2014
DOI: 10.1002/jcla.21665
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Serum Cystatin C in Predicting Coronary Artery Disease in Patients Without Chronic Kidney Disease

Abstract: Background: Cystatin C has been proposed as a novel marker of renal function and predictor of cardiovascular risk. The aim of this study was to investigate the role of cystatin C level as a predictor of cardiovascular events in patients with coronary artery disease (CAD). Methods: Three hundred and five coronary artery patients were included in this study. Serum cystatin C levels, highsensitive C-reactive protein (hs-CRP), and oxidative stress were measured. Estimated glomerular filtration rate (eGFR) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…rs2074381 of ALPK1 was significantly associated with CAD and ischemic stroke, with the GG genotype being protective against these conditions. These previous observations (27,41,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) and our present results suggest that ALPK1 may contribute to the development of CAD and ischemic stroke through the acceleration of vascular inflammation, although the molecular mechanisms underlying the role of rs2074381 of ALPK1 in the pathogenesis of CAD and ischemic stroke remain unknown.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…rs2074381 of ALPK1 was significantly associated with CAD and ischemic stroke, with the GG genotype being protective against these conditions. These previous observations (27,41,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) and our present results suggest that ALPK1 may contribute to the development of CAD and ischemic stroke through the acceleration of vascular inflammation, although the molecular mechanisms underlying the role of rs2074381 of ALPK1 in the pathogenesis of CAD and ischemic stroke remain unknown.…”
Section: Discussionsupporting
confidence: 79%
“…The serum concentration of cystatin C was thus associated with those of C-reactive protein and fibrinogen in 990 subjects with coronary heart disease in the Heart and Soul Study (43), as well as in subjects with renal dysfunction in the Cardiovascular Health Study (44). Furthermore, the serum concentration of cystatin C was associated with the prevalence and severity of CAD (45)(46)(47), the risk of secondary cardiovascular events (48,49) and cardiovascular mortality (50). Cystatin C was also associated with ischemic and hemorrhagic stroke (51) and subclinical cerebral infarction (52).…”
Section: Discussionmentioning
confidence: 97%
“…It is known that inflammation plays a role in pathogenesis of onset and progression of atherosclerosis . C‐reactive protein (CRP) and albumin are indicators of inflammation and are both associated with atherosclerosis and CAD . Current data regarding the prognosis in critical illnesses and malignancies suggest that C‐Reactive Protein/Albumin Ratio (CAR) reflects the balance between CRP and albumin levels and has prognostic significance based on systemic inflammation …”
Section: Introductionmentioning
confidence: 99%
“…Inflammation plays an important role in the development of atherosclerosis. 11 Dandana et al 13 showed that cystatin C was correlated with the CAD severity score and associated with biochemical atherosclerosis markers such as hs-CRP and homocysteine.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been studied for its role in predicting new-onset or deteriorating cardiovascular disease (CVD). [11][12][13] Cystatin C is a nonglycosylated low-molecular-weight (13 kD) basic protein that inhibits cysteine proteases and correlates closely to glomerular filtration rate (GFR) in children. 14 Cystatin C crosses the glomerular membrane, and it is reabsorbed and metabolized in the renal tubules and not returned to the bloodstream.…”
Section: Introductionmentioning
confidence: 99%